2022
DOI: 10.1155/2022/7684076
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Preliminary Imaging Study of [188Re]Re‐Ibandronate as a Novel Theranostic Radiopharmaceutical for Bone Metastasis

Abstract: Background. Bone is a common site of metastasis from a malignant tumor. Several radiopharmaceuticals are available to relieve bone pain in patients with cancer. However, every radiopharmaceutical has its own disadvantages, and there is still a need to investigate easily accessible and high bone affinity radiopharmaceuticals. Ibandronate (IBA) and 188Re were used for radiolabeling to develop and evaluate a novel type of bone-seeking radiopharmaceutical. Methods. The preparation conditions of [188Re]Re-IBA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…68 Ga-DOTA-IBA was rapidly metabolized in vivo and aggregated in bone metastases after IV injection. This is similar to the previously reported biodistribution of radionuclide-labeled ibandronate ( 177 Lu and 188 Re), 13,19 although where the bifunctional chelate DOTA was not used to bind ibandronate. In the imaging time point used in this study, there was no decreasing trend in SUV of bone metastases, but considering the effect of 68 Ga half-life, it is recommended that the imaging time point should be set at 2 hours.…”
Section: Discussionsupporting
confidence: 90%
“…68 Ga-DOTA-IBA was rapidly metabolized in vivo and aggregated in bone metastases after IV injection. This is similar to the previously reported biodistribution of radionuclide-labeled ibandronate ( 177 Lu and 188 Re), 13,19 although where the bifunctional chelate DOTA was not used to bind ibandronate. In the imaging time point used in this study, there was no decreasing trend in SUV of bone metastases, but considering the effect of 68 Ga half-life, it is recommended that the imaging time point should be set at 2 hours.…”
Section: Discussionsupporting
confidence: 90%
“…Ibandronic (IBA) acid is a third generation bisphosphonate. Studies have reported the labelling of metal ions with IBA acid using complex methods requiring larger amounts of precursors and products that have toxic side effects ( 6 , 7 ). Previous studies have shown that the bifunctional chelate DOTA can be used for the complexation of metal compounds ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the development of 188 Re in nuclear medicine has been slow, with few innovative studies being reported [ 68 , 69 , 70 ]. However, the research on radioactive rhenium has not stopped.…”
Section: Study On Re In Cancer Therapymentioning
confidence: 99%